Distributed electrical resources with micro hydroelectric power plants in Colombia — Study case. (November 2021) - Espinel, Alvaro; Díaz, Iván; Vega, Adriana
Abstract: Energy coming from large hydroelectric plants is recognized worldwide due to the great environmental impact caused by the deviation of the rivers during the construction period and the dams while they are operating. This paper shows the design and construction of a micro hydroelectric power plant (MHPP) that was carried out in Cundinamarca Department, in Colombia, in order to analyze the feasibility of generating electric power with micro-power plant, which can be dispatched to the National Interconnected System, taking into account technical and economic aspects for the recovery of the investment. On the other hand, different scenarios are considered, such as self-consumption or the sale of energy to users of the rural sector that are close to the project, performing the financial analysis with economic indicators such as Internal Rate of Return, Uniform Annual Equivalent Cost and Net Present Value. These types of initiatives take special relevance in Colombia because the country issued Law 1715 of 2014, whose purpose is to improve energy reliability, it supports these kinds of projects with tax incentives such as: Discount of Value Added Tax (19%), 50% deduction of the income tax for up to five (5) years and elimination of the tariff levies for the equipment that make up the project. Based on the considerations above and because of the testing of the 24 kVA micro hydroelectric power plant, a paper that deals with the entire construction process of the micro-plant has been prepared, which includes: Flow capacity, turbine selection, selection of the generator, design of the electrical installations and commissioning to verify the effective value of the energy generated and the feasibility of being dispatched to the National Interconnected System.